Perbedaan Tingkat Pengetahuan Ibu Hamil Sebelum danSetelah diberikan Penyuluhan tentang AnemiaGizi Besi dengan menggunakan Media Booklet diPuskesmas Gatak - Wijayanti, Astriani, Muwakhidah, SKM, M.Kes, Rustiningsih, SKM., M.Kes (2015)
Background : Anemia is the greatest health problem in the world, especially in pregnant mothers and majority is caused by iron deficiency. Poor knowledge about anemia is also one of indirect causes of anemia. Thus, we need to increase pregnant mothers' knowledge. Education is one of efforts to make society behave or adopt healthy behaviors. Objective : This study aimed to find the difference between knowledge level of pregnant mothers before and after getting nutrition education about irondeficiency anemia using booklet at Public Health Center of Gatak. Research Method : This research was a quasi experimental with the research plans of one group pretest-posttest design. The subjects of this research were 46 pregnant mothers who were invited to Public Health Center of Gatak. The data were collected using questionnaire. The technique of analyzing data used paired t-tests. Results : Before the nutrition education was given only 41,3% of pregnant mothers had good knowledge and 58,7% had poor knowledge. Meanwhile, after receiving the nutrition education, 95,7% of pregnant mothers had good knowledge and 4,3% had poor knowledge. There was difference between the knowledge level of pregnant mothers before and after receiving nutrition education (p= 0,000). Conclusion: There was a difference between knowledge level of pregnant mothers before and after receiving nutrition education about iron-deficiency anemia using booklet at Public Health Center of Gatak.